PELATIHAN KETERAMPILAN KOMUNIKASI DAN PELAYANAN PELANGGAN BAGI PENGUSAHA PARIWISATA DI DESA WARNASARI: STRATEGI PENINGKATAN KUALITAS LAYANAN WISATA - Gojali, Taufan; Permana, Ibar Adi; Nurvianti, Elmi; Setiawati, Popong; Nunung, Ai (JURNAL ABDIMAS PLJ, 2025)
The purpose of this Community Service (PKM) program is to provide knowledge and communication and customer service skills to tourism entrepreneurs in Desa Warnasari, Kecamatan Pengalengan, Kabupaten Bandung, West Java. The communication and customer service skills training program aimed at tourism entrepreneurs in Desa Warnasari was carried out as a strategy to improve the quality of tourism services. The training activities are designed with a participatory approach through lecture methods, role simulations, and question and answers. The results of the evaluation showed an increase in participants' understanding of the importance of interpersonal communication in the context of tourism services as well as improving attitudes and service practices to tourists. This training makes a significant contribution to shaping the image of a friendly and quality tourism destination, while strengthening local competitiveness in the midst of the growth of the tourism industry. These findings underscore the importance of investing in tourism human resource capacity development as an integral part of sustainable destination management strategies.